A system to prevent social violence using convolutional neural network - Akter, Sanzida; Omar, Mostafa Nayeem; Siam, Aanan Ehsan; Rahman, Fariha; Tanjib, Sadib (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.